REFLECTION OF MUTHAHHARI MURTADHA THOUGHTS: Methodology, Epistemology and Thought Agenda - Zainal Abidin (State Institute of Islamic Studies (IAIN) Palu, 2019)
Murtadha Mutahhari as a great Islamic figure and thinker has attracted the interest of many experts. This research is a research that also examines how the views of Murtadha Mutahhari in three major aspects, namely methodology, epistemology and agenda of thought. This research is a study of figures with a focus on thinking developed by Murtadha Mutahhari. The study of the thoughts of Mutahhari Mutahhari is carried out through a study of his works and the thoughts or views of experts regarding Mutahhari Murtadha. The results of this study indicate that Murtadha Mutahhari can elaborate rational-philosophical thinking with a strong religious understanding and produce an active style of thinking and in accordance with the current civilization.